Broadcasting Bidirectional Access Network Intrusion Detection System Facing Tri-Networks Integration - Han Qiu; Julong Lan; Yangfeng Ou; Chuanhao Zhang; Yanhong Wang (Dianxin kexue)
China’s broadcasting bidirectional access network now rarely takes effective measures to protect its boarder safety. In view of this situation，a network intrusion detection system for the border safety was proposed and an example product called SunGnet703 was given. The system can detect network attacks passing through the border in real time with four notable features，non-aided deployment，high reliable operation，not able to be detected to ensure its own safety and fu11 data collection，and hopefully it can give a simple and easy-to-accomplish solution to protect the border safety.